Models of printed boards for solderless mounting of electronic components by foil perforation method - Yefimenko, A. A.; Paliukh, B. P. (Technology and design in electronic equipment, 2017)
The paper presents models of printed circuit boards for an improved foil perforation method. The density of electrical connections of such printed circuit boards is estimated in comparison with circuit boards obtained using the methods of mounting in holes and surface mounting. The technological differences in the manufacture of printed circuit boards for the foil perforation method and the traditional method are considered.